Gendering the Everyday in the UK House of Commons - Miller, Cherry M. author. aut Link
XVI, 323 p. 3 illus.
Keywords: This book explores the reproduction of gender ‘beneath the spectacle’ – that is, beneath ceremonial displays of power, in the UK House of Commons. Contributing to a fascinating literature on gender and parliaments, the book conceives of the House of Commons as a workplace, as well as a representative arena. It explores the everyday consequences for gendered power relations that this unique environment entails, as parliamentary actors perform their careers, citizenship, and public service. The book firstly explores ways to conceive of and to study gender in parliaments. Parliamentary ethnography – that is, spending time observing and engaging with parliamentary actors, is presented as an unparalleled methodology to better understand gender, power, and agency. The chapters that follow provide in-depth portrayals of gender and the parliamentary workplace. The book connects multiple actors in the House of Commons: MPs, officials, parliamentary researchers, and the (in)formal rules that structure the relationships between them. Dr. Cherry M. Miller is Postdoctoral Researcher at Tampere University, Finland. She was the winner of the 2019 European Consortium of Political Research, Joni Lovenduski PhD Prize in Gender and Politics. Her research is published in the European Journal of Politics and Gender, Parliamentary Affairs, and Political Studies Review.